Preliminary evaluation on the EMT6 breast tumor inhibitory activity of carbon nanotubes with hyperthermia - Muhammad Redza, Mohd Radzi; Wan Fatin Amira, Wan Mohd Zawawi; Nurliyana, Ahmad Zawawi; Khairunadwa, Jemon (AIP Publishing, 2021)
Breast cancer is considered one of the most dangerous types of cancer with a high mortality rate among women worldwide. Potential alternative treatments such as hyperthermia (HT) often associated with poor specific heat distribution within the tumor microenvironment, thus reducing its anticancer potential. Owing to the fact that CNTs possessed high thermal conductivity, which could provide a uniform heat distribution, this study aims at exploring the combined effect of CNTs and HT in managing breast tumors. In this study, multiwalled CNTs were functionalized by acid washing protocol and validated by characterization analysis. Female Balb/c mice were inoculated with EMT6 breast cancer cells and then were intratumorally injected once with MWCNTs before being subjected to HT treatment for 3 consecutive days. Tumor progression and survival curves of mice were monitored. Our results demonstrated a successful functionalization of MWCNTs throughout dispersion, FTIR, TGA, XRD and FESEM analysis. Moreover, the combined-treated tumor showed complete eradication and prolonged survival median. The histological data revealed that combined treatment induced significant tumor necrosis post-treatment. Altogether, results from this preliminary study suggested that functionalized CNTs in combination with HT demonstrated a promising effect in eliminating EMT6 breast tumor.